Analysis of Fixed Asset Management by Indonesian Local Governments - Apriliani, Lili; Rizqi, Rania; Grabriella, Stefany; Muharrammaini, Ulfa; Nasution, Anggi Pratama (CV Raskha Media Group, 2025)
The management of fixed assets is a vital component of the governance of local government finances as it relates to the accountability and quality of local government financial reports. This study aims to analyse the management of fixed assets by local governments in Indonesia and the level of compliance with the Government Accounting Standards Statement (PSAP) 07 and the changes in regulation from Minister of Home Affairs Regulation Number 19 of 2016 to Minister of Home Affairs Regulation Number 7 of 2024. The research method used is a qualitative approach with literature review method by analysing scientific journals, research reports and relevant legislation. The results of the study indicate that, normatively, local governments have implemented PSAP 07 in recognition and presentation of fixed assets in the local government financial statements. However, the implementation of fixed asset management is suboptimal which is characterised by problems in asset identification, inconsistency of physical and administrative data, weak legal asset protection, limited information systems, and low competency of the managing human resources. The enactment of Permendagri Number 7 of 2024 brings increased demands for the integration of asset management systems, control, and optimisation of the use of regional assets, but in its initial implementation phase, it still requires adjustments to the institution and the strengthening of the capacity of local government officials. The research examines the systems employed by local governments in the management of public sector assets, the impact of human resources on the management of such assets, and the local governments' compliance with established regulations.